The Relationship Between Constipation and Physical Activity and the Recurrence of Hemorrhoids in the Working Area of Pelambuan Public Health Center, Banjarmasin - Wati, Irma; Afriyanti, Uni; Rosefa, Wika Rispudyani; Sary, Era Widia (Papua Medicine and Health Science, 2025)
Lifestyle changes and demographic shifts have contributed to the rising prevalence of non-communicable diseases in developing countries, one of which is hemorrhoids. Hemorrhoids are a common anorectal condition with a high recurrence rate, influenced by factors such as constipation and physical activity. Constipation increases intra-abdominal pressure during defecation, while low levels of physical activity slow intestinal motility. Additionally, vigorous physical activity can increase pressure on the hemorrhoidal veins due to excessive strain on the anal region. This study aimed to examine the relationship between constipation and physical activity and the recurrence of hemorrhoids in the working area of Pelambuan Public Health Center, Banjarmasin. A correlational analytic design with a cross-sectional approach was used, involving a total sampling of 83 respondents with a history of hemorrhoids. Data were collected using a constipation questionnaire based on the Rome III criteria and the Global Physical Activity Questionnaire (GPAQ). Analysis using the Spearman’s Rank Correlation Test showed a significant relationship between constipation and hemorrhoid recurrence (p = 0.000 < α = 0.05), as well as between physical activity and hemorrhoid recurrence (p = 0.000 < α = 0.05). It can be concluded that both constipation and physical activity are significantly associated with hemorrhoid recurrence. Individuals with hemorrhoids are advised to consume high-fiber foods, maintain regular bowel habits, and perform vigorous physical activities properly as preventive measures against recurrence.